On Competition and the Strategic Management of Intellectual Property in Oligopoly - Jos Jansen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
An innovative firm with private information about its indivisible process innovation chooses strategically whether to apply for a patent with probabilistic validity or rely on secrecy. By doing so, the firm manages its rivals' beliefs about the size of the innovation, and affects the incentives in the product market. A Cournot competitor tends to patent big innovations, and keep small innovations secret, while a Bertrand competitor adopts the reverse strategy. Increasing the number of firms gives a greater (smaller) patenting incentive for Cournot (Bertrand) competitors. Increasing the degree of product substitutability increases the incentives to patent the innovation.
urn:nbn:de:bvb:19-epub-13215-4
Keywords: D82; L13; O31; O32; 330; Bertrand and Cournot competition; oligopoly; productdifferentiation; Immaterielle Güter; Innovation; Prozessmanagement; Patent; Asymmetrische Information; Duopol